Lonestar Angel - Coble, Colleen (Nashville, Tenn. : Thomas Nelson, 2011)
When Eden Larson's estranged husband, Clay, delivers the news that their lost baby girl who was kidnapped years earlier may have been found, the couple's love for each other is rekindled as they investigate.
Keywords: Married people -- Fiction; Camp counselors -- Fiction; Missing children -- Fiction; Texas -- Fiction; Christian fiction; Romantic suspense fiction